Pengembangan Big Book Untuk Meningkatkan Keterampilan Membaca Permulaan - Hasanah, Nurdina; Zunidar, Zunidar (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to develop Big Book to improve elementary school students' initial reading skills. This research is a type of Research and development (R&D) with a 4D model (Define, Design, Development, & Dissemination). Data collection techniques are carried out through structured interviews, non-participant observations, questionnaires, pre-tests, post-tests, and documentation. The Big Book design developed has been declared valid by experts with a Material Expert Assessment Percentage of 90% (Very Valid) and a Media Expert Assessment Percentage of 90% (Very Valid). The students' responses showed practicality with a percentage of 75.1% (Practical), and the results of the practitioners' assessment showed a percentage of 92.2% (Very Practical). The results of the pre-test and post-test of grade I students of SDN 094102 Sambosar showed an increase in N-Gain of 82%, which is in the high category. Thus, Big Book was declared effective in improving beginner reading skills. This study concludes that the development of Big Book effectively improves elementary school students' initial reading skills. The limitation of this study is that it is only conducted in one school (SDN 094102 Sambosar) and one class (grade I), so it is difficult to generalise these results to other schools and classes. Further research is recommended to involve more than one school to test the generalisation of results for different schools.